If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2ab(5a + -7b) = 0 (5a * 2ab + -7b * 2ab) = 0 Reorder the terms: (-14ab2 + 10a2b) = 0 (-14ab2 + 10a2b) = 0 Solving -14ab2 + 10a2b = 0 Solving for variable 'a'. Factor out the Greatest Common Factor (GCF), '2ab'. 2ab(-7b + 5a) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'ab' equal to zero and attempt to solve: Simplifying ab = 0 Solving ab = 0 Move all terms containing a to the left, all other terms to the right. Simplifying ab = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-7b + 5a)' equal to zero and attempt to solve: Simplifying -7b + 5a = 0 Reorder the terms: 5a + -7b = 0 Solving 5a + -7b = 0 Move all terms containing a to the left, all other terms to the right. Add '7b' to each side of the equation. 5a + -7b + 7b = 0 + 7b Combine like terms: -7b + 7b = 0 5a + 0 = 0 + 7b 5a = 0 + 7b Remove the zero: 5a = 7b Divide each side by '5'. a = 1.4b Simplifying a = 1.4bSolution
a = {1.4b}
| x/2-x/3=5/6 | | 7(x^2-4)+2x=2(x-4) | | 8x^3+20x^3+12x=0 | | u^2-10u+25= | | 2-3h=10-5h | | 10-6t=-8-9t | | 8-8x=1-3x | | 4=-v+v/-8 | | -7-5u=-7u+9 | | 4a^2-9a+2=0 | | 9+3g=4g | | 6y+5=4y-9 | | -4-9=-2 | | 5(6x-5)=1-1x | | -5n=5-10n | | 4b+10=-10+2b | | -5w-10=3w+6 | | 8x=100+3x | | 5x+35=2(x+8) | | 2r-6=3r | | S=187+0.225S | | 10-2z=-7z | | -f+3=-4f | | 7*3x=6x+9 | | x+1/3+x-2/6=x+6/12 | | -6j-8=-8j | | 1/4d+3/4=6 | | x+6/3+x-2/6=2x-3/12 | | 27=2-5(9-x) | | 3(t+1)=9 | | 1/2h-16=5/8h | | 8h+(-15h)+(-5)=(-19) |